2021
DOI: 10.1007/s10549-021-06309-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, treatment patterns, and prognosis of low estrogen receptor-positive (1% to 10%) breast cancer: a single institution’s experience in Korea

Abstract: Purpose: To determine prevalence, clinicopathological characteristics, initial treatments, and outcomes associated with low estrogen receptor (ER)-expressing invasive breast cancer.Methods: This retrospective, noninterventional database study included patients undergoing surgery with curative intent for invasive ductal or lobular breast cancer. Patients were treated between January 2003-December 2012. Demographics, clinicopathologic characteristics, initial treatments, and outcomes were abstracted from patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Our findings are in line with other studies, which have likewise shown comparable pathological response rates and survival for Low-ER breast cancer and TNBC 18 , 23 26 . In our cohort, only nodal positivity and higher T stage (and not ER/PR expression group) were significantly associated with RFS and OS on multivariable analysis, consistent with previous work 24 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in line with other studies, which have likewise shown comparable pathological response rates and survival for Low-ER breast cancer and TNBC 18 , 23 26 . In our cohort, only nodal positivity and higher T stage (and not ER/PR expression group) were significantly associated with RFS and OS on multivariable analysis, consistent with previous work 24 .…”
Section: Discussionsupporting
confidence: 93%
“…Our study does have limitations, including the relatively small number of patients in the Low-ER group and lack of central testing for ER/PR. The Low-ER subgroup comprised 12.6% of our study population; this finding is consistent with previous studies which have shown that this group accounts for 8–16% of HER2-negative ER/PR-negative breast cancers, with different definitions of ER/PR negativity being utilized across studies 18 , 23 , 24 . Although lack of central ER/PR testing may be considered a limitation, utilization of local testing is representative of the real-world setting.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In NeoPACT, 16% of enrolled patients had low ER−PR (1%-10%), and we noted comparable pCR rates between patients with low vs negative ER−PR. A growing body of literature indicates that HER2/ERBB2 negative, low ER−PR breast cancer displays clinical characteristics, chemotherapy response, and outcomes similar to TNBC . The low ER−PR group comprises 8% to 16% of HER2/ERBB2 negative breast cancer and is often excluded from TNBC clinical trials, thus limiting efficacy data for newer therapies in this group .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies demonstrated that patients with ER low-positive HER2-negative breast cancer have similar outcomes as compared to triple-negative breast cancer (TNBC) patients 10 14 . ER low-positive breast tumors have comparable progesterone receptor (PR) levels 12 , 15 , tumor grade 10 13 , 16 and Ki-67 expression 11 , 13 , 16 to TNBC and are usually classified as basal-like or HER2-enriched 11 , 15 , 17 . Intermediate ER expression of 10–50% is common in ~5–10% of breast tumors 18 , 19 and we hypothesize that this group might share basal-like features with TNBC similar to the ER low-positive group.…”
Section: Introductionmentioning
confidence: 99%